The glass-transition temperature and both the topological and chemical thresholds in chalcogenide glasses - Tichý, Ladislav; Tichá, Helena (Univerzita Pardubice, 1996)
The problem of the glass-transition temperature (Tg) is discussed using the idea of the topological and chemical threshold in chalcogenide glasses. Within a simple covalent bond approach it is shown that the short range bonding arrangement mainly determines the Tg values in chalcogenide glasses. Good correlation between Tg and the overall mean bond energy, (〈E〉), of a covalent network of a glass was found for 186 binary and ternary chalcogenide glasses. This correlation satisfies the Arrhenius relation for viscosity, where the apparent activation energy of viscosity is empirically related to the overall mean bond energy.